Penguatan Ecological Citizenship Mahasiswa Melalui Pendidikan Kewarganegaraan: Membangun Kesadaran dan Tanggung Jawab Mahasiswa Terhadap Lingkungan - Fahmi, Rizal; Nanggala, Agil; Hidayah, Nurul (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The increasingly complex ecological crisis demands a reorientation of citizenship from a mere relation of political-juridical rights and obligations toward moral responsibility for the environment. This community service activity aimed to strengthen ecological citizenship among students of the Primary School Teacher Education Program at Universitas Pendidikan Indonesia Cibiru Campus through an online public lecture on integrating ecological values into Civic Education. The activity employed interactive lectures, guided discussions, and structured reflection through a video-conferencing platform. Evaluation used pre-activity and immediate post-activity questionnaires to identify short-term changes in understanding, attitudes, and behavioural intention, not long-term ecological action. The results indicate an initial improvement in participants' understanding of ecological citizenship, awareness of their connectedness to the more-than-human community, and commitment to integrating environmental education into Civic Education practice in primary schools. The activity served as an entry point for forming the ecological identity of prospective primary teachers and requires institutional follow-up through curriculum integration, campus habituation, and practice-based programs.